Investments And Bureaucratic Barriers: The Effect Of Property Ownership In The Manufacturing Industry Of Arequipa City 2024 - Mujica Calderón, Jaime (2025)
This article analyzes how property ownership influences the reduction of bureaucratic barriers that affect private investment in small and medium-sized enterprises (SMEs) in Arequipa in 2024. It identifies that deficiencies in the property registration system, managed by SUNARP, COFOPRI, and Bienes Nacionales, create obstacles for SME growth by increasing costs, procedures, and legal uncertainty. Using a quantitative approach, it was evidenced that property ownership has a significant impact on operational efficiency and access to capital for these businesses, with a determination coefficient of 0.3906. The article proposes the need for a comprehensive reform to improve interinstitutional coordination and the implementation of modern technologies to streamline and make registration processes more transparent. This proposal aims to foster a more favorable environment for investment and SME development in Arequipa.